The effect of seasonal change of plants compositions on visual perception - Eroğlu, Engin; Müderrisoğlu, Haldun; Kesim, Güniz Akıncı (Journal of Environmental Engineering and Landscape Management, 2012)
Plants are important elements of open-green areas in the urban space and perception of an environment. Some plants have seasonal colour changes. The identification of these changes and clarification of the effects on people are quite important for landscape architecture. Seasonal changes of plants in some open-green areas in Düzce were examined in order to explain how it affects people regarding changes in perceptional preferences. Delphi Method was used on photographs as a mean of identification of the visual effects of the plant compositions. The plant composition photographs, which had been examined before, were used in the questionnaire to 370 student groups. As a result, the difference was evaluated between the perceiving of different plant compositions. Summer was the most affecting season having the design value and visual quality. Besides, evergreen plants had a positive effect on design power and visual quality of compositions. Furthermore, as another important result, it was found out that socio-economic levels of the people had some important effects on visual preferences. In this study, perceptional differences of the participants on seasonal changes of the plants were identified. Moreover, the form and the texture were evaluated for identifying perceptional effects.Article in English.Sezoninio augalijos sudėties pokyčio įtaka vizualiam suvokimuiSantrauka. Reikšmingas urbanizuotos teritorijos elementas yra želdynų augalija. Kai kurios augalų rūšys kintant sezonui keičia spalvas. Suvokiant šių pokyčių poveikį žmogui, svarbu tai pritaikyti kuriant kraštovaizdžio architektūrą. Sezoninių augalijos pokyčių poveikiui tirti pasirinkta ãtviros Düzce apylinkių vietos. Vizualiam augalijos poveikiui nustatyti taikytas Delphi fotonuotraukų metodas. Anksčiau vertintos nuotraukos buvo panaudotos apklausoje, kurioje dalyvavo 370 studentų grupių. Vertinti augalijos skirtingos sudėties suvokimo skirtumai. Nustatyta, kad didžiausią poveikį vizuali želdinių projektavimo kokybė daro vasaros sezoną. Respondentai, vertindami projektavimą ir vizualią augalijos sudėties kokybę, teigiamai pažymėjo visžalius augalus. Iš apklausų nustatyta, kad didelę įtaką vizualiam suvokimui turi socialiniai-ekonominiai žmonių skirtumai. Įvertinta ir projektuojamų želdinių formos bei sandaros reikšmė suvokiant vaizdo efektus.Reikšminiai žodžiai: augalai, sezoninis pokytis, vizualus suvokimas, semantinė diferencinė skalė, kraštovaizdžio architektūra